Health effects and economic losses due to PM2.5 pollution from oil consumption by mobile sources in China - Lin, Yibin; Xi, Yanling; Chen, Jiabin; Cui, Yanfang; Wang, Zengchuan; Ren, Chenxu (Frontiers in Environmental Science, 2025)
While oil remains a critical component of global energy systems, its combustion in the transport sector releases fine particulate matter (PM2.5), posing significant public health risks. As previous studies have overlooked the health impacts and economic losses associated with PM2.5 pollution from oil consumption by mobile sources, this article analyzes the annual average concentration of PM2.5 in China’s provinces for key years from 2020 to 2060. It then assesses the projected health effects and economic losses resulting from PM2.5 pollution linked to provincial oil consumption during these key years, utilizing an integrated exposure–response relationship (IER) model and the revised human capital method. The results show that the health effects of PM2.5 pollution—specifically on lung cancer, chronic obstructive pulmonary disease (COPD), ischemic heart disease (IHD), and stroke—vary significantly by province: in 2020, lung cancer deaths were highest in Shandong Province (1,317 cases), followed by Henan Province (1,206 cases), and lowest in Tibet (only 7 cases projected in 2060); premature deaths from COPD were particularly prominent in Shandong Province (1,615 cases in 2020) and are projected to peak in Guangdong Province in 2035); and premature deaths from stroke were particularly prominent in Shandong Province (1,615 cases in 2020), while Guangdong Province is expected to surpass Shandong after 2035. Premature deaths due to stroke were most severe in Shandong Province (5,284 cases in 2020), followed by Henan and Jiangsu provinces. As annual average PM2.5 concentrations decrease, the number of premature deaths in China is also projected to decrease, but the economic losses due to premature death are greatest in the middle-aged and older age groups (50–74 years). In 2020, lung cancer and COPD accounted for $151.988 billion in losses in the 65–69 years age group, and stroke caused the highest economic losses ($31.81 billion); by 2050, IHD is projected to top the list of economic losses ($24.01 billion), while COPD is expected to consistently result in the lowest economic losses. This study provides a quantitative basis for optimizing the energy structure and formulating regionally differentiated emission reduction policies.